Time series and spatial interaction: An alternative method to detect converging clusters - Stilianos Alexiadis; Matthias Koch; Tamás Krisztin (European Regional Science Association (ERSA), 2011)
In this paper an attempt is made to assess the hypothesis of re- gional club-convergence, using a spatial panel analysis combined with B-Splines. In this context, a `convergence-club' is conceived as a group of regions that in the long-run move towards steady-state equilib- rium, approximated in terms of the average per-capita income. Using data for the US states over the period 1929-2005, a pattern of club- convergence is detected. The 'cluster' of converging states is rather limited and a strong spatial component is detected.
Keywords: 330